THE IRANIAN-PAKISTANI FACTOR IN THE GEOPOLITICS OF CENTRAL AND SOUTH ASIA - YULDASHEVA, Gouli (CENTRAL ASIA AND THE CAUCASUS, 2014)
The author has chosen Iran and Pakistan, two giants of the Muslim world, as the subject of her analysis and identifies their place in the context of the geopolitical changes underway in Central and South Asia. She investigates in detail the degree to which their interests are intertwined, as well as the extent of their interaction with other actors (the U.S., Russia, China, India, Saudi Arabia, Afghanistan, and the Central Asian republics). She also points to the potentially useful factors that might eventually help to overcome all the challenges, risks, and threats that, so far, remain prominent enough to slow down progress in the relations between Iran and Pakistan. The talks between the West and Iran, which have been going on far too long and complicated by the Ukrainian crisis and the rapidly approaching NATO drawdown from Afghanistan, are further destabilizing the already destabilized situation in the AfPak zone. This negatively affects the relations between the two countries, their potential impact on the Central Asian region, and the prospects for the geoprojects related to them.